Developing countries in the process of economic globalisation - Bernhard Fischer (Intereconomics, 1990)
The last decade has witnessed the emergence of a more global economy reflecting the continued rise in trade (especially of manufactures) as a proportion of output, a major shift of international specialisation, faster diffusion of technical progress and the globalisation of financial markets. What have been the effects of this process on developing countries?
Keywords: 330; Integration